Exit, Voice and Loyalty: Responses to Decline in Firms, Organizations, and States. - Tullock, Gordon; Hirschman, Albert O. (Journal of Finance, 1970)
1. Introduction and Doctrinal Background Enter and Latitude for deterioration, and slack in economic thought Exit and voice as impersonations of economics and politics 2. Exit How the exit option works Competition as collusive behavior 3. Voice Voice as a residual of exit Voice as an alternative to exit 4. A Special Difficulty in Combining Exit and Voice 5. How Monopoly Can be Comforted by Competition 6. On Spatial Duopoly and the Dynamics of Two-Party Systems 7. A Theory of Loyalty The activation of voice as a function of loyalty Loyalist behavior as modified by severe initiation and high penalties for exit Loyalty and the difficult exit from public goods (and evils) 8. Exit and Voice in American Ideology and Practice 9. The Elusive Optimal Mix of Exit and Voice Appendixes A. A simple diagrammatic representation of voice and exit B. The choice between voice and exit C. The reversal phenomenon D. Consumer reactions to price rise and quality decline in the case of several connoisseur goods F. The effects of severity of initiation on activism: design for an experiment (in collaboration with Philip G. Zimbardo and Mark Snyder) Index